YbBa2-xSrxCu3O7-delta coated conductor development by sol-gel process - (:unkn) unknown (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2005)
YbBa2-xSrxCu3O7-delta coated conductors were grown on Gd1.8Ho0.2O3 buffer layered biaxially textured-Ni (100) substrates by the reel-to-reel sol-gel dip coating system. Sample with different Sr substitution ratio (x = 0.0, 0.1, 0.2, 0.3, 0.4, and 0.6) were heat treated using varying heat treatment parameters. The surface morphologies and microstructure of all samples were investigated by ESEM, EDS and XRD. The critical current measurements were performed using four-wire method with the 1 mu V/cm criterion. The critical current density, J(c) was measured to be 10(5) A/cm(2) at 4.2 K and 104 A/cm(2) at 75 K in-self field for YbB1.9Sr0.1Cu3O7-delta sample.
Keywords: coated conductors; critical current; sol-gel; Sr doping; YbBCO; NI TAPES; YBA2-XSRXCU3O7-DELTA; DEPOSITION